Strindberg and the Five Senses : Strindberg's Chamber Plays. - Ekman, Hans-Goran (Continuum International Pub. Group, 2000)
In this book, Dr Ekman considers Strindberg's four "Chamber plays" of 1907: "Thunder in the Air", "The Burned Site"," The Ghost Sonata" and "The Pelican."